A Zero-Defect High Sea Sale Automation Framework for Real-Time Ownership Transfer and Compliance in Maritime Trade Systems (International Journal of Engineering & Extended Technologies Research (IJEETR), 2024)
Some of the most complicated legal documents in the international marine industry pertain to High Sea Sale (HSS) transactions. Packed with finance, compliance and legal documentation needs, including international one, each stage of the goods cannot move further until logistic, legal, and financial aspects are synchronized. This is done at the customs level before the cargo is mounted, loaded, signed, declared and transported to its final delivery point. The business environment is no longer tolerant of ‘time wasted’, ‘poor skills’, or ‘the money lost` excuses, or ‘a shrinking market.’ Walking away from this issue is easy, especially when very few presentation or critical demand, consumption or distribution of seismology or nature and culture of marketing for the millennial cobalt age, characteristic of the history of robust military upshifting, are not adequate. Traditional approaches at manually processing HSS are faced with a high likelihood of errors, exposed to high demurrage costs, and experience problems of congestion, thus hindering scale of activities worldwideIn the following paper we will discuss a Zero- Defect High Sea Sale Automation Framework (ZD-HSSAF) that is specifically designed in and deployed in an Oracle R12 enterprise environment of the international logistics department of a global Pharma company – for high-sea practices. The framework involves a 4d dimension electronic declaration with a unique twist to the business rules for such transaction, a virtual high sea sale auto notification tool with gate logics which prevents legal acceptability being extended with issuance of letter of guaranteeIt is empirically proven that the application has improved in agreement processing performance i.e. (throughput) 1400% i.e. processing agreements from 1 per week to 15 per day since 99% of Closed defects were removed in the previous Releases, reached zero post-production tickets, and saved more than USD 1 million dollars annually through removal of port demurrage penalties. On the contrary, the reference provides for wide scale and coordinated use of artificial technical changes under time limits
Keywords: High Sea Sale; Maritime Trade Automation; Oracle R12; Zero-Defect Deployment; Stamp Paper Authentication; Biometric Signature; Ownership Transfer; Digital Compliance; Demurrage Avoidance; IGST; FEMA